Associations among Adolescent Mothers' Environmental Stressors and their Children's Executive Function: Understanding the Role of Maternal Sensitivity - Menon, Meera. (2017)
Abstract: Within my Master's thesis I explored the associations among the exposure to individual level and contextual level stressors early in life and children's executive function (EF) within a population of adolescent mothers. Specifically, I examined maternal sensitivity as mediating the relations between environmental stressors and children's EF. Participants comprising my thesis sample included adolescent mothers and their first-born children who were partaking in an evaluation of a home visiting parenting program, Healthy Families Massachusetts (HFM). Findings indicated that adolescent mothers' earlier sensitive parenting was positively associated with children's EF in early childhood. Additionally, my findings pointed to a non-significant trend between exposure to contextual stressors and children's EF. However, environmental stressors were not associated with maternal sensitivity. As there is a dearth of research examining the nature of the associations among stressors, sensitive parenting and EF for adolescent mothers and their children, my Master's thesis aimed to fill in these gaps in order to promote children's optimal EF development.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Child Study and Human Development.; Advisor: M. Ann Easterbrooks.; Committee: Tama Leventhal, and Stephanie Jones.; Keyword: Developmental psychology.